Some results of oat breeding under the conditions of the Volga-Vyatka region of Russia - G. A. Batalova; I. G. Loskutov (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Along with barley, oat is among the most important food and feed cereals. It is one of the most significant grain crops in world agriculture. Unfortunately, the area under this crop in Russia is steadily decreasing. According to the 2024 data, oats in Russia were sown on a total area of 1.7 million hectares. It is the largest acreage among the world’s countries and second in the aggregate grain production after the European Union. However, Russia has the most favorable soil and climate conditions for growing this economically important crop. With this in view, Russia could win the leadership not only as an oat producer but also as the world’s top exporter of this crop.Results. Since 2024, ‘Kirovsky 2’, a new covered oat cultivar, has been included in the State Register of the Russian Federation and approved for cultivation in the Northwestern, Central, Volga-Vyatka, and Central Black Earth regions of Russia as an outstanding source of high-quality grain and forage biomass. This new cultivar of covered oat is resistant to lodging, exhibits practical resistance to loose smut and crown rust, shows tolerance to damage by the frit fly, and is weakly affected by root rot. Barley yellow dwarf virus (BYDV) was not observed on its plants.Conclusion. Thus, a new competitive covered oat cultivar was released for food and feed uses, combining high yield with high quality of grain and forage biomass, adapted to the conditions of the Northwestern, Central, Volga-Vyatka, and Central Black Earth regions of Russia. Russian breeding centers can include this cultivar into the breeding process to obtain promising genotypes of covered oat for introduction into agricultural production.